Discussion—Mathematics, Realism and Management Sciences - Greenhut, Melvin L. (Management Science, 1958)
In a paper which appeared in the 1957 edition of this journal (Weinwurm, Ernest H. 1957. Limitations of the scientific method in management science. Management Sci. (April) 225–233.), Professor Weinwurm suggests that the use of mathematics in management science may so dominate a given model as to cause the disregard of vital human values. He cites Professor Bodenhorn who warns that the trend toward mathematical frameworks in economics may be associated with an application of good mathematical assumptions but poor economics (Bodenhorn, Diran. 1956. The problem of economic assumptions in mathematical economics. J. Political Econom. (February) 25–32.). In some dispute with Professor Flood's philosophy (Flood, Merrill M. 1956. The objective of TIMS. Management Sci. (January) 178–183.), he feels that we cannot ignore the nonquantitative factors in human relations.